(untitled) (The Strategic Review for Southern Africa, 2020)
This article outlines several categories of Private Military Companies(PMCs) to distinguish between the different military services these organisations provide. In doing so, the article argues that an appropriate category is needed to understand the military operations these companies undertake. The article suggests that the PMCs can be divided into four categories: the Combat Offensive PMC, the Combat Defensive PMC, the Non-Combat Offensive PMC, and finally the Non-Combat Defensive PMC